Hybrid three-dimensional representation based on panoramic images and three-dimensional models for a virtual museum: Data collection, model, and visualization. (April 2017) - Hu, Qingwu; Yu, Dengbo; Wang, Shaohua; Fu, Caiwu; Ai, Mingyao; Wang, Wende
As an important part of the public service and educational infrastructures for national culture and heritage culture, a virtual museum presents the user experience of a real museum, with visitors, educators, and tourists interacting with the prepared digital culture contents by a mouse, touch panel, and other augmented reality devices. The goal of virtual museum is to help students and visitors to move around the virtual museum space freely and generate experience and satisfaction from the fruition of cultural heritage anytime, anywhere, and from any device. This study presents a hybrid three-dimensional virtual museum based on panoramic images and three-dimensional models. A technical framework of hybrid three-dimensional virtual museum is proposed on the basis of a typical three-tier architecture, which includes the data layer, technique supporting layer, and application layer. A hybrid three-dimensional data organization approach with geo-referenced sequence panoramic images and three-dimensional models is designed to build the data layer of hybrid three-dimensional virtual museum. A three-dimensional scene of geo-referenced sequence panoramic images and three-dimensional models is created in real time using Unity three-dimensional and web service under the mobile Internet environment for hybrid three-dimensional virtual museum. The different applications of hybrid three-dimensional virtual museum based on the data layer and technique infrastructure are designed to achieve handheld virtual museum guidance and navigation, three-dimensional browsing, and heritage culture information query for visitors with smartphones to access anytime and anywhere. As an example, a hybrid three-dimensional virtual museum application for Jinsha Archaeological Site Museum is developed with the proposed approach. The geo-referenced sequence panoramic images of museum galleries, together with three-dimensional models of cultural relics, can integrate seamlessly to a three-dimensional reality-based museum space where users can move around the space actively and freely with all kinds of personal computer and smartphone clients.